POTENSI WISATA ALAM GUNUNG TELETUBIS DI DESA AVOLUA KECAMATAN PARIGI UTARA KABUPATEN PARIGI MOUTONG - Rahmawati, Desi; Korja, I Nengah; Toknok, Bau; Rosyid, Abdul (Universitas Tadulako, 2021)
Teletubis mountain yootism object is one of attractions found in parigi moutong regency precisely mouton regency precisely in avolua village kecamatan north parigi central sulawesi province this research there are several types of animals such as butterflies, dragonflies, snails. Not only fauna there are also flora such as reeds, Javanese wood, gersen, coconut, and guava there are alsobeautiful natural scenery and still very good for tourists to visit inside and outside the city tourists to visit inside and outside the city tourists can tae a trip by approaching to reach the summit of teletubis mountain in the village of avolua, north parigi sub-district, parigi mouton district was conducted in april to may 2019 located in teletubis mountain tourism object avolua village, north parigi sub-district, parigi moutong district, central sulawesi province, the purpose of this study was to determine the village of avolua, nirth parigi district, the method used in this research was ADO-ODTWA analysis. This tourist attraction has the potantial for the uniaveness of attractive natural resources such as flora and fauna, natural. Phenomena as well as beatiful panorama, security, and comfort that is aviceawoke, good service and the availability of facilites and infrastructure. So this attraction is worth developing with the acauisition of eligibility index 74,76%, the strategy that must be carried oul for the development of natural tourism is the feasibility of existing netural rosoorces, make additions to existing and non, existent faciuties such as gazebos and trashbins inceriase promotion to tourists by teletubis mountain publishing them to print and social media.Keyword: Teletubis mountain, nature tourism, mountain